CLASSROOM MANAGEMENT STRATEGIES FOR EFFECTIVE TEACHING AND LEARNING IN UNIVERSITIES IN RIVERS STATE, NIGERIA - Amini-Philips, Chinyere (PEOPLE: International Journal of Social Sciences, 2019)
The study investigated classroom management strategies teachers in Universities implement for effective teaching and learning. Five objectives, research questions and hypotheses respectively guided the study. The descriptive survey research design was adopted with the sample of the study consisting of 59teachers and 394students drawn from three public universities in Rivers State. The multi-stage sampling technique was used to draw the sample and a questionnaire designed in line with the 4-point Likert scale of ‘Strongly Agree’ to ‘Strongly Disagree’ was administered. The reliability of the instrument was ascertained by use of Cronbach Alpha technique and are liability index of 0.92 was obtained, indicating a high consistency of the instrument. Mean and Standard deviation were used to answer the research questions while the hypotheses were tested at 0.05 level of significance using t-test. The finding showed that teachers and students acknowledged the strategies delineated as those implemented by teachers with respect to: classroom arrangement, expectations from students, and strategies to promote appropriate use of consequences. The researcher concluded that teaching and learning is being carried out effectively in Rivers State Universities and therefore recommended that teachers be encouraged to sustain the adoption of classroom management strategies by recognizing and rewarding hardworking teachers.